Essential Oils and Their Application in Food Safety - Maurya, Akash; Prasad, Jitendra; Das, Somenath; Dwivedy, Abhishek Kumar (Frontiers in Sustainable Food Systems, 2021)
Food industries are facing a great challenge due to contamination of food products with different microbes such as bacteria, fungi, viruses, parasites, etc. These microbes deteriorate food items by producing different toxins during pre- and postharvest processing. Mycotoxins are one of the most potent and well-studied toxic food contaminants of fungal origin, causing a severe health hazard to humans. The application of synthetic chemicals as food preservatives poses a real scourge in the present scenario due to their bio-incompatibility, non-biodegradability, and environmental non-sustainability. Therefore, plant-based antimicrobials, including essential oils, have developed cumulative interest as a potential alternative to synthetic preservatives because of their ecofriendly nature and generally recognized as safe status. However, the practical utilization of essential oils as an efficient antimicrobial in the food industry is challenging due to their volatile nature, less solubility, and high instability. The recent application of different delivery strategies viz. nanoencapsulation, active packaging, and polymer-based coating effectively addressed these challenges and improved the bioefficacy and controlled release of essential oils. This article provides an overview of essential oils for the preservation of stored foods against bacteria, fungi, and mycotoxins, along with the specialized mechanism of action and technological advancement by using different delivery systems for their effective application in food and agricultural industries smart green preservative.